4-Pentenoic acid exhibits broad-spectrum antibacterial activity against foodborne pathogens by disrupting bacterial membrane integrity and inhibiting efflux pump systems - Jiaming Mu; Jie Li; Fushuang Duan; Rui Wen; Xuepeng Cai; Qingling Meng; Jun Qiao; Zhongmei Ma (International Journal of Food Microbiology, 2026)

Integrative genetic analysis reveals shared genetic architecture underlying coronary artery disease, CT-Defined coronary atherosclerosis, and cardiometabolic risk factors - Yao Zhao; Yingying Xie; Didi Wen; Jin Zhang; Ziliang Xu; Zhibin Wu; Jiaming Li; Yuanqiang Zhu; Minwen Zheng (Functional & Integrative Genomics, 2026)

A kidney-targeted MOF nanozyme combats calcium oxalate crystal-induced kidney injury - Xuhong He; Min Zhou; Zhengxin Liang; Shiyi Jin; Kunze Yu; Longxiyu Meng; Zhicong Tan; Jinming Xu; Jiaju Xu; Chongjun Xiang; Jingchao Wei; Wenjun Gao; et al. (Chemical Engineering Journal, 2026)

Molecularly functionalized high-Q THz metasurface via q-BIC for selective HbA1c detection - Chang Liu; Min Gao; Zichen Zhang; Junxiao Liu; Ligeng Jin; Xin Tian; Lijun Jiang; Zhongmei Zheng; Chuanyue Li; Jiaming Feng; Xingyu Liao; Zhihang Long; et al. (Chemical Engineering Journal, 2026)

Assessment of laterization degree of tropical residual laterites overlying carbonate rocks in Yunnan, China - Haiyan Gao; Zhongxin Deng; Zemin Xu; Yixi Wen; Jiaming Zhang; Jipu Chen; Lin Tian (CATENA, 2026)

BnaCIPK9 homoeologs mediate the dosage-dependent regulation of seed oil in allotetraploid Brassica napus L - Nan Wang; Jingquan Tang; Xianfei Hou; Chengtao Quan; Jiaming Mai; Chao He; Rundong Chen; Baolong Tao; yuanguo Gu; Donghai Jia; Tingdong Fu; Jitao Zou; et al. (Theoretical and Applied Genetics, 2026)

Collaboration of the symbiotic microbiome and host genome during the high altitude adaptation of chickens - Jiaming Jin; Chaoliang Wen; Junying Li; Chunning Mai; Jingwei Yuan; Ping Wang; Da Peng; Yiqiang Zhao; Congjiao Sun; Xueying Ma; Jing Feng; Ning Yang (Science China Life Sciences, 2026)

Non-uniform salinity combined with localized nitrogen supply improves water use efficiency and fruit visual and storage qualities in tomato - Jinjing Liu; Zhenchang Wang; Yongfeng Huang; Yuexiong Wang; Weixing Wen; Kexin Chen; Yanmin Bi; Yating He; Jiaming You; Yaosheng Wang (Plant and Soil, 2026)

Transcriptomic and metabolomic analysis reveals the effect of hydrogen sulfide on delaying fruit ripening and color transition of white fleshed strawberry (Fragaria ananassa) - Miao Sun; Yue Wen; Xuanhuan Qiao; Tao Yang; Peng Zhao; Junhao Zhao; Jiaming Luo; Jialun Zhang; Zhipeng Zhu; Weijian Cai; Meng Xu; Li Yao; et al. (Postharvest Biology and Technology, 2025)

A normalized small waterbody size transition index for remote sensing drought monitoring - Xi Wang; Wen Zhang; Junjie Li; Zhe Wang; Zhen Zhang; Hui Wang; Yanjiao Song; Jiaming Chen; Yi Bao; Bingsun Chen; Qianyu Wang; Jia Chen; et al. (Journal of Hydrology, 2025)

Predictive biomarkers for valproic acid-induced hepatotoxicity in Chinese patients with epilepsy: the role of metabolites and genetic polymorphisms - Dingsheng Wen; Zhuojia Chen; Ziyi Chen; Xue Bai; Hongliang Li; Juan Chen; Qiling Dai; Guoping Zhong; Jiaming Qin; Guanzhong Ni; Min Huang; Liemin Zhou; et al. (Food and Chemical Toxicology, 2025)

Investigation of nTiO2-WTe2 (n = 1–3) nanocluster sensors for the detection of toxic gases H2S, NH3, and NO2 in agricultural greenhouses: A DFT study - Haoming Zhang; Jiaming Jiang; Wen Zhou; Qu Zhou (Journal of Environmental Chemical Engineering, 2025)

Engineering cuttlefish melanin nanoparticles: A dual-action therapy for acute radiation syndrome and combined radiation-wound injuries via regulating Bcl-2 family proteins and caspases in the apoptotic process - Zhemeng Zhao; Bin Hu; Danfeng Zhang; Xinyue Cui; Wen Ding; Tongshuai Wang; Jingyi Wang; Ziyi Guo; Yingtang Zhou; Shige Wang; Jiaming Guo (Chemical Engineering Journal, 2025)

Efficient Removal of Cr(VI) by Bamboo-Derived Biochar Supported Nano Zero-Valent Iron: Insights into Performance and Mechanism - Yiqun Xu; Jiaming Guo; Siqi Wen; Xiaoyu Shi; Yunlong Zhu; Jianbing Lu; Yang Gao; Mingjuan Zhang; Wenjing Xue (Water, Air, & Soil Pollution, 2025)

Intergenerational differences and influencing factors of farmers’ terrace abandonment behavior: Based on a questionnaire survey of 2382 rural households in China - Jiaming Wen; Shilong Luo; Hualin Xie; Xiubin Li (Journal of Geographical Sciences, 2025)

Achieving remarkable charge transfer through the depolarization field in the 2D/2D S-scheme heterojunction consisted of C3N5 nanosheets and layered ferroelectric Bi3TiNbO9 for photocatalytic hydrogen production - Haotian Guo; Jinhui Jiang; Jiaming Liang; Chunyang Wen; Xinguo Xi; Pengyu Dong (Chemical Engineering Journal, 2025)

Evaluation of a novel attapulgite loaded sulfidized nanoscale zero-valent iron for immobilization of Pb in sediment: Performance, microenvironmental response, and mechanisms - Siqi Wen; Weilong Lin; Qi He; Yiqun Xu; Xiaoyu Shi; Jiaming Guo; Yang Gao; Wenjing Xue (Chemical Engineering Journal, 2024)

Amino-modified biochar-supported S-nZVI for Cr(VI) and total Cr removal from water: Parameter regulation, kinetic and mechanistic analysis - Yiqun Xu; Jiaming Guo; Siqi Wen; Xiaoyu Shi; Qi He; Weilong Lin; Yu Wang; Yang Gao; Rongzhong Wang; Wenjing Xue (Journal of Water Process Engineering, 2024)

LSGNet: A lightweight convolutional neural network model for tomato disease identification - Shengxian Yang; Licai Zhang; Jianwu Lin; Tomislav Cernava; Jitong Cai; Renyong Pan; Jiaming Liu; Xingtian Wen; Xiaoyulong Chen; Xin Zhang (Crop Protection, 2024)

Genome-wide identification and expression analysis of the SOD gene family under biotic and abiotic stresses in sweet orange - Xulin Li; Ke Wen; Tuo Yin; Chaoying Chen; Ling Zhu; Xiuyao Yang; Yinqiang Zi; Ke Zhao; Jiaming Zhang; Hanyao Zhang (Plant Biotechnology Reports, 2024)

High performance self-assembled sulfidized nanoscale zero-valent iron for the immobilization of cadmium in contaminated sediments: Optimization, microbial response, and mechanisms - Yiqun Xu; Hongdou Liu; Siqi Wen; Jiaming Guo; Xiaoyu Shi; Qi He; Weilong Lin; Yang Gao; Rongzhong Wang; Wenjing Xue (Journal of Hazardous Materials, 2024)

Affecting factors and mechanism of removing antibiotics and antibiotic resistance genes by nano zero-valent iron (nZVI) and modified nZVI: A critical review - Wenjing Xue; Xiaoyu Shi; Jiaming Guo; Siqi Wen; Weilong Lin; Qi He; Yang Gao; Rongzhong Wang; Yiqun Xu (Water Research, 2024)

Long-term exposure to the mixture of phthalates induced male reproductive toxicity in rats and the alleviative effects of quercetin - Li-Lan Liu; Jun-Zhe Yue; Zhen-Yu Lu; Ru-Ya Deng; Can-Can Li; Ye-Na Yu; Wen-Jin Zhou; Min Lin; Hai-Tao Gao; Jiaming Liu; Ling-Zi Xia (Toxicology and Applied Pharmacology, 2024)

Activation of persulfate by biochar-supported sulfidized nanoscale zero-valent iron for degradation of ciprofloxacin in aqueous solution: process optimization and degradation pathway - Wenjing Xue; Xinyu Chen; Hongdou Liu; Jun Li; Siqi Wen; Jiaming Guo; Xiaoyu Shi; Yang Gao; Rongzhong Wang; Yiqun Xu (Environmental Science and Pollution Research, 2024)

Enhanced immobilization of cadmium in contaminated paddy soil by biochar-supported sulfidized nanoscale zero-valent iron - Yiqun Xu; Shan Cao; Xinyu Chen; Jun Li; Hongdou Liu; Yang Gao; Siqi Wen; Jiaming Guo; Xiaoyu Shi; Wenjing Xue (Journal of Soils and Sediments, 2024)

Immobilization of cadmium in river sediments by different modified nanoscale zero-valent iron: performance, mechanisms, and Fe dissolution - Wenjing Xue; Hongdou Liu; Jun Li; Xinyu Chen; Siqi Wen; Jiaming Guo; Xiaoyu Shi; Shan Cao; Yang Gao; Rongzhong Wang; Yiqun Xu (Environmental Science and Pollution Research, 2023)

Recent advances in sulfidized nanoscale zero-valent iron materials for environmental remediation and challenges - Wenjing Xue; Jun Li; Xinyu Chen; Hongdou Liu; Siqi Wen; Xiaoyu Shi; Jiaming Guo; Yang Gao; Jian Xu; Yiqun Xu (Environmental Science and Pollution Research, 2023)

Multiscale Feature Fusion for Hyperspectral Marine Oil Spill Image Segmentation - Guorong Chen; Jiaming Huang; Tingting Wen; Chongling Du; Yuting Lin; Yanbing Xiao (Journal of Marine Science and Engineering, 2023)
Oil spills have always been a threat to the marine ecological environment; thus, it is important to identify and divide oil spill areas on the ocean surface into segments after an oil spill accident occurs to protect the marine ecological environment. However, oil spill area segmentation using ordinary optical images is greatly interfered with by the absorption of light by the deep sea and the distribution of algal organisms on the ocean surface, and it is difficult to improve segmentation accuracy. To address the above problems, a hyperspectral ocean oil spill image segmentation model with multiscale feature fusion (MFFHOSS-Net) is proposed. Specifically, the oil spill segmentation dataset was created using hyperspectral image data from NASA for the Gulf of Mexico oil spill, small-size images after the waveband filtering of the hyperspectral images were generated and the oil spill images were annotated. The model makes full use of having different layers with different characteristics by fusing feature maps of different scales. In addition, an attention mechanism was used to effectively fuse these features to improve the oil spill region segmentation accuracy. A case study, ablation experiments and model evaluation were also carried out in this work. Compared with other models, our proposed method achieved good results according to various evaluation metrics.

Association between mercury exposure and lung function in young adults: A prospective cohort study in Shandong, China - Jiaming Miao; Shurong Feng; Siqi Dou; Yang Ma; Liu Yang; Lailai Yan; Pei Yu; Yao Wu; Tingting Ye; Bo Wen; Peng Lu; Shanshan Li; et al. (Science of The Total Environment, 2023)

From remotely‐sensed solar‐induced chlorophyll fluorescence to ecosystem structure, function, and service: Part II—Harnessing data - Ying Sun; Jiaming Wen; Lianhong Gu; Joanna Joiner; Christine Y. Chang; Christiaan van der Tol; Albert Porcar‐Castell; Troy Magney; Lixin Wang; Leiqiu Hu; Uwe Rascher; Pablo Zarco‐Tejada; et al. (Global Change Biology, 2023)
Although our observing capabilities of solar‐induced chlorophyll fluorescence (SIF) have been growing rapidly, the quality and consistency of SIF datasets are still in an active stage of research and development. As a result, there are considerable inconsistencies among diverse SIF datasets at all scales and the widespread applications of them have led to contradictory findings. The present review is the second of the two companion reviews, and data oriented. It aims to (1) synthesize the variety, scale, and uncertainty of existing SIF datasets, (2) synthesize the diverse applications in the sector of ecology, agriculture, hydrology, climate, and socioeconomics, and (3) clarify how such data inconsistency superimposed with the theoretical complexities laid out in (Sun et al., 2023) may impact process interpretation of various applications and contribute to inconsistent findings. We emphasize that accurate interpretation of the functional relationships between SIF and other ecological indicators is contingent upon complete understanding of SIF data quality and uncertainty. Biases and uncertainties in SIF observations can significantly confound interpretation of their relationships and how such relationships respond to environmental variations. Built upon our syntheses, we summarize existing gaps and uncertainties in current SIF observations. Further, we offer our perspectives on innovations needed to help improve informing ecosystem structure, function, and service under climate change, including enhancing in‐situ SIF observing capability especially in “data desert” regions, improving cross‐instrument data standardization and network coordination, and advancing applications by fully harnessing theory and data.

From remotely sensed solar‐induced chlorophyll fluorescence to ecosystem structure, function, and service: Part I—Harnessing theory - Ying Sun; Lianhong Gu; Jiaming Wen; Christiaan van der Tol; Albert Porcar‐Castell; Joanna Joiner; Christine Y. Chang; Troy Magney; Lixin Wang; Leiqiu Hu; Uwe Rascher; Pablo Zarco‐Tejada; et al. (Global Change Biology, 2023)
Solar‐induced chlorophyll fluorescence (SIF) is a remotely sensed optical signal emitted during the light reactions of photosynthesis. The past two decades have witnessed an explosion in availability of SIF data at increasingly higher spatial and temporal resolutions, sparking applications in diverse research sectors (e.g., ecology, agriculture, hydrology, climate, and socioeconomics). These applications must deal with complexities caused by tremendous variations in scale and the impacts of interacting and superimposing plant physiology and three‐dimensional vegetation structure on the emission and scattering of SIF. At present, these complexities have not been overcome. To advance future research, the two companion reviews aim to (1) develop an analytical framework for inferring terrestrial vegetation structures and function that are tied to SIF emission, (2) synthesize progress and identify challenges in SIF research via the lens of multi‐sector applications, and (3) map out actionable solutions to tackle these challenges and offer our vision for research priorities over the next 5–10 years based on the proposed analytical framework. This paper is the first of the two companion reviews, and theory oriented. It introduces a theoretically rigorous yet practically applicable analytical framework. Guided by this framework, we offer theoretical perspectives on three overarching questions: (1) The forward (mechanism) question —How are the dynamics of SIF affected by terrestrial ecosystem structure and function? (2) The inference question : What aspects of terrestrial ecosystem structure, function, and service can be reliably inferred from remotely sensed SIF and how? (3) The innovation question : What innovations are needed to realize the full potential of SIF remote sensing for real‐world applications under climate change? The analytical framework elucidates that process complexity must be appreciated in inferring ecosystem structure and function from the observed SIF; this framework can serve as a diagnosis and inference tool for versatile applications across diverse spatial and temporal scales.

In-depth understanding of catalytic and adsorbing effects in polysulfides conversion and rationally designing coaxial nanofibers for Li-S batteries - Jiaming Tian; Zihan Shen; Huiting Cheng; Xin Jin; Zhonghua Li; Yang Wen; Junfeng Hui; Shaohua Guo; Huigang Zhang; Qingshan Zhu (Chemical Engineering Journal, 2023)

Selection and truncation of aptamers as fluorescence sensing platforms for selective and sensitive detection of nitrofurazone - Xu Wen; Xueling Yan; Xiaoling Zheng; Qiming Kou; Lulan Yang; Jiaming Tang; Xingyue Chen; Yong Xie; Tao Le (Analytica Chimica Acta, 2023)

MOF-derived ultrasmall Ru@RuO2 heterostructures as bifunctional and pH-universal electrocatalysts for 0.79 V asymmetric amphoteric overall water splitting - Zhe Li; Jizhao Zou; Tao Liang; Xinrui Song; Zhangjian Li; Jiaming Wen; Minggui Peng; Xierong Zeng; Haitao Huang; Hongliang Wu (Chemical Engineering Journal, 2023)

Brain microstructural alterations in the left precuneus mediate the association between KIBRA polymorphism and working memory in healthy adults: a diffusion kurtosis imaging study - Junxia Wang; Sichu Wu; Yi Sun; Jiaming Lu; Jilei Zhang; Yu Fang; Zhao Qing; Xue Liang; Wen Zhang; Qian Chen; Xin Zhang; Bing Zhang (Brain Imaging and Behavior, 2022)
Kidney and brain expressed protein (KIBRA) rs17070145 is associated with working memory function and cognitive processes. However, the neural mechanisms underlying these associations are not fully understood. This study aimed to explore the effect of KIBRA polymorphism on brain microstructure and blood oxygenation level dependent (BOLD) fluctuations using diffusion kurtosis imaging (DKI) and resting-state functional magnetic resonance imaging (fMRI) in 163 young adults. We also investigated that whether the imaging alterations mediated the association between KIBRA gene and working memory performance. Voxel-based analysis of DKI data showed that KIBRA C-allele carriers exhibited increased axial diffusivity (AD), radial diffusivity (RD) and mean diffusivity (MD) as well as decreased fractional anisotropy (FA), mean kurtosis (MK) and radial kurtosis (RK) compared with KIBRA TT homozygotes, primarily involving the prefrontal lobe, left precuneus and the left superior parietal white matter. Meanwhile, KIBRA C-allele carriers exhibited decreased amplitude of low-frequency fluctuation (ALFF) in the left precuneus compared to KIBRA TT homozygotes. Mediation analysis revealed that the DKI metrics (MK and RK) of the left precuneus mediated the effect of the KIBRA polymorphism on working memory performance. Moreover, the MK and RK in the left precuneus were positively correlated with ALFF in the same brain region. These findings suggest that abnormal DKI parameters may provide a gene-brain-behavior pathway in which KIBRA rs17070145 affects working memory by modulating brain microstructure in the left precuneus. This illustrates that DKI may provide additional biological information and reveal new insights into the neural mechanisms of the KIBRA polymorphism.